2018
DOI: 10.2478/ausm-2018-0012
|View full text |Cite
|
Sign up to set email alerts
|

An efficient numerical method for solving nonlinear Thomas-Fermi equation

Abstract: In this paper, the nonlinear Thomas-Fermi equation for neutral atoms by using the fractional order of rational Chebyshev functions of the second kind (FRC2), ${\rm{FU}}_{\rm{n}}^\alpha \left( {{\rm{t}},{\rm{L}}} \right)$ (t, L), on an unbounded domain is solved, where L is an arbitrary parameter. Boyd (Chebyshev and Fourier Spectral Methods, 2ed, 2000) has presented a method for calculating the optimal approximate amount of L and we have used the same method for calculating the amount of L. With the aid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Table 2 presents the absolute error of HSE with Adomian's method. A comparison of proposed technique is presented in Table 3 with the existing numerical techniques, Haar wavelet quasi-linearization method [29], a collocation method [52] and Chebyshev functions (B-GFCF) collocation method [53]. It is concluded that our proposed technique provides the better results on the basis of absolute errors.…”
Section: Casementioning
confidence: 93%
See 1 more Smart Citation
“…Table 2 presents the absolute error of HSE with Adomian's method. A comparison of proposed technique is presented in Table 3 with the existing numerical techniques, Haar wavelet quasi-linearization method [29], a collocation method [52] and Chebyshev functions (B-GFCF) collocation method [53]. It is concluded that our proposed technique provides the better results on the basis of absolute errors.…”
Section: Casementioning
confidence: 93%
“…Furthermore, iterative methods like, variational iteration method (VIM), modified variational iteration method (VMIM), Adomian decomposition method (ADM), modified Adomian decomposition method (MADM) and Homotopy analysis method (HAM) are described [23]. The reciprocal transformations [24], Homotopy decomposition method [25], bivariate generalized fractional order of the Chebyshev functions (BGFCF) [26], cubic trigonometric B-Spline collocation method [27], collocation method [28], Harr wavelet quasilinearization approach [29], and Lipschitz metric [30], time marching scheme [31] are applied to study the diffusion of neumatic LCs. The generalized Hunter-Saxton equation is considered using integrability structures [32], Numerical solutions of HSE using Laguerre wavelet and by using efficient approach on time domains is presented in [33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The Thomas-Fermi (T-F) equation is a nonlinear singular differential equation defined on a semi-infinite domain [23,24] as…”
Section: Thomas-fermi Equationmentioning
confidence: 99%
“…Using the routine PLeal2 from Appendix C, we obtain ̃1( ) and ̃2( ), using [0, 12,12] and [4, 10, 10] as the order for expansions, respectively; Considering the expansion points [0, 1, 5] for ̃1( ) and [5,10,25] for ̃2( ). The numerical values [23] employed as expansions points for LP, are…”
Section: Thomas-fermi Equationmentioning
confidence: 99%
See 1 more Smart Citation